2014
DOI: 10.1002/ajh.23765
|View full text |Cite
|
Sign up to set email alerts
|

IPSS‐R in 555 Taiwanese patients with primary MDS: Integration of monosomal karyotype can better risk‐stratify the patients

Abstract: The revised International Prognostic Scoring System (IPSS-R) was recently developed to better assess the clinical outcome of adult patients with myelodysplastic syndrome (MDS). In this study, we aimed to investigate the prognostic impact of this new risk model on 555 MDS patients in Taiwan. Generally, the IPSS-R could discriminate MDS patients regarding risk of leukemia evolution and overall survival in our cohort and it further refined prognostic stratification in all IPSS risk categories. However, we could n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 24 publications
2
29
1
Order By: Relevance
“…Koenecke et al reported that MK is a negative predictor of outcome in the poor risk group (but not the very poor risk group) of the IPSS‐R classification in MDS patients after HSCT. In publications on Asian populations, MKs had an independent adverse prognostic value . For example, a Korean report noted that MKs may predict poor survival but for non‐CK status only .…”
Section: Discussionmentioning
confidence: 99%
“…Koenecke et al reported that MK is a negative predictor of outcome in the poor risk group (but not the very poor risk group) of the IPSS‐R classification in MDS patients after HSCT. In publications on Asian populations, MKs had an independent adverse prognostic value . For example, a Korean report noted that MKs may predict poor survival but for non‐CK status only .…”
Section: Discussionmentioning
confidence: 99%
“…3). The median age at diagnosis seems to vary in different countries, being lower in "Eastern" than in "Western" countries: 59 years old in China [22], 60 in Japan [24], 58 in Korea [25], 56 in Thailand [26], and 65 in Taiwan [27], 77 in US [28], 72-73 in Germany [15,16,29], and 65-71 in Italy [15,16,30,31]. However, a new report using a population-based registry data showed a median age of 76 years for Japan [32].…”
Section: Discussionmentioning
confidence: 99%
“…32 The predictive value of cytogenetic information for outcome after allogeneic SCT has been reported by others, not only for the 3-group-IPSSclassification, 33 but also for the 5-group IPSS-R-classification. [13][14][15] In all studies, unfavorable cytogenetic information, as classified according to the IPSS or IPSS-R classification, predicted worse patient outcome. However, this study is the first to evaluate formally the added value of the 5-group IPSS-R classification compared to the 3-group classification in the setting of SCT for predictive performance and to show that the relevant distinction in categories in this context is standard-poor-very poor when other risk factors are taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…number of marrow blasts, time from diagnosis to transplant, prior chemotherapeutic treatment and remission status), the karyotype of the disease seems to be most predictive for relapse-free survival (RFS) after transplantation. [5][6][7][8][9][10][11][12][13][14][15] However, most studies used the International Prognostic Scoring System (IPSS) cytogenetic risk score (good, intermediate, and poor cytogenetic risk groups) for the analysis of relapse and OS after SCT in MDS patients. 16 In 2012, a new 5-group cytogenetic scoring system with a refined cytogenetic risk prediction in MDS patients not undergoing SCT was proposed.…”
Section: Introductionmentioning
confidence: 99%